TRAINING OF FUTURE SPECIALISTS FOR THE FORMATION OF THE FOUNDATIONS OF MEDIA LITERACY OF CHILDREN OF PRESCHOOL AND PRIMARY SCHOOL AGE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In connection with the digitization of the educational process, the need for the development of critical thinking of children of senior preschool and junior school age, the development of the ability to use information in any form, to communicate, and to understand the consequences of interaction in the digital world is increasing. The article proves that media literacy of a modern people is the basis of their security in the information society. It is found out that the training of future specialists in preschool and primary education should include the formation and development of methodological competence of students for the formation of media literacy and information culture of children of preschool and junior school age, as well as the creation of an educational and informational environment in a preschool education institution. Emphasis is placed on solving the following tasks: to form the ability to implement a systematic approach to the introduction of media education in preschool and primary school; to form the ability to protect children from an aggressive media environment; to form the ability to use media technologies in order to organize media creativity of children of senior preschool and junior school age; to form a certain level of information culture of future specialists; to instill future educators’ creative approach to the formation of the foundations of children’s information culture; to form the need for future preschool and primary education specialists in self-education in accordance with the requirements of the information society. In the course of this study, we used the following methods: theoretical: analysis of scientific sources to determine the state of research on the problem of forming media literacy of preschool children and training future preschool education specialists to form media literacy of children. Synthesis, systematization and generalization of theoretical provisions of the problem were used; empirical: pedagogical observation of children's activities in 18 preschool education institutions, conversations with preschool education teachers regarding the implementation of activities to form the foundations of media literacy of preschool children, conversations with students about the relevance of the problem of forming media literacy of preschool children, questionnaires of future preschool education specialists of the Mykhailo Kotsiubynskyi Vinnytsia State Pedagogical University. The experimental study was conducted, the respondents of which were bachelor’s degree holders of the specialty 012 Preschool Education and 013 Primary Education of Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University. The following approaches and technologies for the formation of future specialists of preschool and primary education in the ability to form the foundations of media literacy and information culture of children of preschool and senior school age have been singled out: a problem-based approach, BYOD - technology (“bring your own device”), the method of “inverted learning”.